The Contribution of Transpersonal Psychology to The Emotional, Mental, and Spiritual Well-Being of Individuals - Haryanto, Sri; Muslih, Mohammad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
This research explores the impact of transpersonal psychology on the emotional, mental, and spiritual well-being of individuals. The study aims to understand how mindfulness, meditation, and holotropic therapy contribute to holistic well-being. Using a qualitative phenomenological approach, the research involved 20 participants, 12 males and eight females, aged between 25 and 60 years, from various holotropic therapy centers, meditation communities, and mindfulness groups across different ethnicities in Indonesia, including Javanese, Sundanese, and Balinese. Key informants included experts in transpersonal psychology; supporting informants were individuals directly engaged in these practices. Data were collected through in-depth interviews and participatory observation, then analyzed using thematic analysis with NVivo software. The findings indicate that transpersonal psychology significantly enhances participants' overall well-being by providing tools for deeper self-exploration, trauma healing, and spiritual development. Practices like mindfulness and meditation fostered present-moment awareness and emotional balance, while holotropic therapy facilitated access to higher states of consciousness and emotional processing. Integrating these practices into daily life helped individuals maintain a connection with their transpersonal awareness, even amidst daily challenges. This study underscores the importance of a holistic approach in psychology that includes the spiritual dimension, offering insights into how transpersonal psychology can support comprehensive personal growth and well-being.